Plyometric training performance in elite-oriented prepubertal female gymnasts - Marina, M.; Jemni, M. (The Journal of Strength and Conditioning Research, 2014)
We studied the effectiveness of a combined strength and plyometric training program (experimental period) on jumping performance when compared with a training routine on apparatus (control period) over 2 successive gymnastics training seasons. Nine female elite-orientated gymnasts (around 30-hour training per week) were participated in the study. The study was based on a 20-month longitudinal design covering 2 training seasons separated by a competitive period and transition periods. Each season included 1 control and 1 experimental period (Ctrld1 + Exd1 and Ctrld2 + Exd2, respectively). Before and after each control and experimental period, we assessed plyometric performance by means of drop jumps (DJs) from 20, 40, 60, 80, and 100 cm. The jump performance variables considered were flight time (FT), contact time (CT), flight-contact ratio (FC), and estimated mechanical power (also called Bosco expression [BE]), all of which were expressed as raw data and normalized (expressed as a percentage) with respect to the recordings at the beginning of each period of analysis. Flight time was the only variable to increase not only during both experimental periods but also during both controls. Our results confirmed larger relative increments of all the variables (FT, CT, BE, and FC), except for CT at DJs of 80 and 100 cm, during the experimental periods than during their respective previous control periods. Despite the additive effect of growth, development, and maturation, the gymnasts were not able to maintain the DJ performance accomplished during Ex?1, thereby confirming detraining during the competitive and transition periods. We conclude that a combination of heavy resistance training with high impact plyometric jumps is effective in prepubertal gymnasts, despite their initial high level of physical conditioning.